The Effect of Ethanol Extract of Kersen Leaf (Muntingia Calabura L.) on Reducing Triglyceride Levels in Hypercholesterolemic Rats - Imaniar Ranti; Nur Vickasari (HM Publisher, 2022)
Background: Kersen leaf has the potential to lower triglycerides because they contain flavonoids and tannins. Methods: This study was an experimental laboratory study with a pre and post-test with a control group design. The subjects were 30 white male rats (Rattus norvegicus), bodyweight ±200 grams, aged 3-4 months, and divided into 5 groups with random sampling. The groups were negative control (K-) was given a high-fat diet, and PTU without any treatment, positive control (K+) was given a high-fat diet, and PTU with gemfibrozil treatment, (P1),(P2),(P3) was given a high-fat diet and PTU with ethanol extract of Kersen leaf 100, 200, and 400 mg/kgBB. This study was held for 4 weeks. Triglyceride level was measured using the GPO-PAP method. The data was analyzed using Shapiro-Wilk, Levene test, and ANOVA test. Results: The ethanol extract of Kersen leaf dose 100, 200 and 400 mg/kgWB are found effective on reducing blood triglyceride levels with a mean reduction in the first treatment of 112,83 mg/dl, 98,20 mg/dl, 89,92 mg/dl and in the second treatment of 106,71 mg/dl, 93,95 mg/dl dan 76,87 mg/dl. Statistical analysis using one-way ANOVA showed p<0,05, which determines a significant difference in triglyceride levels among each group. Conclusion: Extract dose of 400 mg/kgWB is found to be the most effective dose in triglyceride reduction.